Korean Housing Cycle: Implications for Risk Management (Factor-augmented VAR Approach) - Hyuck-Shin Kwon; Doo Won Bang; Myeong Hyeon Kim (KDI Journal of Economic Policy, 2017)
This paper proposes an integrated risk-management framework that includes 1) measuring the risk of credit portfolios, 2) implementing a (macro) stress test, and 3) setting risk limits using the estimated systematic latent factor specific to capture the housing market cycle. To this end, we extract information from a set of real-estate market variables based on the FAVAR methodology proposed by Bernanke, Boivin and Eliasz (2005). Then, we show the method by which the estimated systematic factor is applied to risk management in the housing market in an integrated manner within the Vasicek one-factor credit model. The proposed methodology is well fitted to analyze the risk of slow-moving and low-defaultable forms of capital, such as alternative investments.
Keywords: R3; E17; G32; 330; Housing Cycle; FAVAR; Risk Management